2021
DOI: 10.1073/pnas.2103154118
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 escape from a highly neutralizing COVID-19 convalescent plasma

Abstract: To investigate the evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the immune population, we coincupi bated the authentic virus with a highly neutralizing plasma from a COVID-19 convalescent patient. The plasma fully neutralized the virus for seven passages, but, after 45 d, the deletion of F140 in the spike N-terminal domain (NTD) N3 loop led to partial breakthrough. At day 73, an E484K substitution in the receptor-binding domain (RBD) occurred, followed, at day 80, by an insertio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
186
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(192 citation statements)
references
References 52 publications
(55 reference statements)
6
186
0
Order By: Relevance
“…In support of this theory, co-evolution of separate virus lineages around the globe (Alpha: lineage B.1.1.7 or 501Y.V1 in the UK; Beta: lineage B.1.351 or 501Y.V2 in the Republic of South Africa; and Gamma: lineage P.1 or 501Y.V3 in Brazil) appear to carry one or more of the same mutations in RBD: K417N/T, E484K, and N501Y (Table 3). Similar mutations were observed to occur in forced viral evolution experiments using convalescent or vaccinee serum; passage of prototype virus with high-titer neutralizing antisera yielded a mutant virus carrying similar NTD deletions and the RBD-specific E484K mutation 45 . Mutation at the E484 site was shown to impact virus neutralization of the ancestral B.1 virus, which has been noted as a concern for emerging variants 44,[46][47][48] (Table 3), although recent epidemiological trends show prevalence for the Delta (B.1.617.2) variant that lacks this mutation (https://www.who.int/en/activities/tracking-SARS-CoV-2-variants/).…”
Section: Rbd May Be Undergoing Convergent Evolutionsupporting
confidence: 58%
“…In support of this theory, co-evolution of separate virus lineages around the globe (Alpha: lineage B.1.1.7 or 501Y.V1 in the UK; Beta: lineage B.1.351 or 501Y.V2 in the Republic of South Africa; and Gamma: lineage P.1 or 501Y.V3 in Brazil) appear to carry one or more of the same mutations in RBD: K417N/T, E484K, and N501Y (Table 3). Similar mutations were observed to occur in forced viral evolution experiments using convalescent or vaccinee serum; passage of prototype virus with high-titer neutralizing antisera yielded a mutant virus carrying similar NTD deletions and the RBD-specific E484K mutation 45 . Mutation at the E484 site was shown to impact virus neutralization of the ancestral B.1 virus, which has been noted as a concern for emerging variants 44,[46][47][48] (Table 3), although recent epidemiological trends show prevalence for the Delta (B.1.617.2) variant that lacks this mutation (https://www.who.int/en/activities/tracking-SARS-CoV-2-variants/).…”
Section: Rbd May Be Undergoing Convergent Evolutionsupporting
confidence: 58%
“…The aforementioned Alpha, Beta, Gamma and Delta variants and the Epsilon variant (B.1.429, California lineage) exhibit decreased sensitivity to neutralization by immune plasma derived from convalescent patients with COVID-19 or vaccinated individuals [40][41][42][43][44][45]185,[189][190][191][192][193][194] . The possibility that these recent variants emerged from the infection of previously infected or vaccinated individuals is supported by studies in which escape variants were experimentally generated in the presence of neutrali zing antibodies, convalescent sera or sera derived from vaccinated individuals [195][196][197][198] . In these studies, the same mutations, including K417N, E484K and N501Y in the RBD, which are the hallmarks of the Alpha, Beta, and Gamma variants, were identified.…”
Section: Immune Escapementioning
confidence: 99%
“…The 484 site mutation also reduced the neutralizing activity of a variety of monoclonal antibodies in clinical stage, including REGN10933 and LY-CoV-555 (2). Some studies have confirmed that the mutation of E484K could eliminate the key interaction between epitope antibodies against 484 and Arg50 or Arg96, resulting in decreased antibody neutralization efficiency (71,72). In contrast, Brii-196, COV2-2130, P2C-1F11, and H014 still preserved high neutralization ability, which may be due to their broad-spectrum antigen-binding epitopes (33,53,73).…”
Section: Mutations In the Rbd Regionmentioning
confidence: 99%
“…E484 position, the targeting site of antibodies such as heavy chain germline IGHV3-53 and IGHV3-66, has the greatest influence on antibody binding and neutralization in RBD region (54,62,69,(74)(75)(76). E484K can escape not only the neutralization of monoclonal antibodies C121, C144 (77) and the serum from convalescent patients (72), but also the neutralization of the combination of REGN10989 and REGN10934 monoclonal antibody cocktail (78).…”
Section: Mutations In the Rbd Regionmentioning
confidence: 99%